Provision of carbohydrate resources to support Apanteles polychrosidis, to increase parasitism of Caloptilia fraxinella in horticultural ash trees - McPike, S. M.; Pain, R. A.; Evenden, M. L. (Frontiers in Ecology and Evolution, 2022)
The provision of nutritional resources for beneficial insects that support pest control, such as parasitoid wasps, is one tactic in conservation biological control. This tactic could be an important element for the development of a biological control program to help control the ash leaf-cone roller, Caloptilia fraxinella Ely (Lepidoptera: Gracillariidae), an introduced pest of horticultural ash trees (Fraxinus) in Canadian Prairie cities, including Edmonton, Alberta. In the current study, we test the efficacy of carbohydrate food provision to support parasitism of C. fraxinella by its primary parasitoid, Apanteles polychrosidis Viereck (Hymenoptera: Braconidae). Laboratory experiments compared the longevity, parasitism rate and offspring fitness of wasps fed sucrose solutions at one of two concentrations (10 and 25% v/v) or flowers of buckwheat, Fagopyrum esculentum (Polygonaceae). Fed wasps lived longer than wasps with access to water only. Mated, but not unmated, males and females lived longer when fed 25% than 10% sucrose. Female A. polychrosidis had similar longevity when fed 25% sucrose or buckwheat flowers. Egg load did not change with sucrose provision. Adult longevity of fed unmated female A. polychrosidis was negatively correlated with egg load. Female A. polychrosidis fed 25% sucrose produced offspring with a slightly female-biased sex ratio and higher fecundity than offspring from female A. polychrosidis fed the 10% sucrose solution.